DRAWING APPLICATION TRAFFIC SIGNS ROADS USING MICROSOFT VISUAL BASIC 6.0 - Ikrar Rifany; Susi Wagiyati. Skom, MM Susi Wagiyati. Skom, MM (Jurnal Sistem Informasi, 2002)
Technological developments in this era is very much interested by all people,especially computers and motor vehicles, therefore encouraging the creation of"Application of Traffic Signs" is because they still lack information about the imageof traffic that is needed by motorists of road users.The computer user is to introduce images of traffic signs based computer that is easyto understand and be understood by its users.